Allotment booking in intermodal transport - Jaržemskienė, Ilona; Jaržemskis, Vytautas (Transport, 2009)
The article presents a valuable concept seeking to solve the problem of demand uncertainty in intermodal transport. Regular traffic is quite important for moving containers, trailers and swap bodies. To keep regularity with uncertain demand means to have backlogs or empty space. Both of them are inefficient from an economical point of view. In practice, a day‐by‐day demand forecast is meaningful only for the next two or three days. This poses serious allotment management problems to freight forwarders and shippers since long‐term contract allotments need to be planned many months ahead. The article presents a stochastic dynamic programming model for a short‐term allotment planning a model that would be very valuable for implementing intermodal solutions. The presented model evaluates optimal cost policy based on the economic trade‐off between the cost of backlogged shipment and the cost of acquiring additional allotment.First published online: 27 Oct 2010